Microbial Consortia for Effective Biocontrol of Root and Foliar Diseases in Tomato - Minchev, Zhivko; Kostenko, Olga; Soler, Roxina; Pozo, María J. (Frontiers in Plant Science, 2021)
The use of beneficial microorganisms for the biological control of plant diseases and pests has emerged as a viable alternative to chemical pesticides in agriculture. Traditionally, microbe-based biocontrol strategies for crop protection relied on the application of single microorganisms. However, the design of microbial consortia for improving the reliability of current biological control practices is now a major trend in biotechnology, and it is already being exploited commercially in the context of sustainable agriculture. In the present study, exploiting the microbial-library of the biocontrol company Koppert Biological Systems, we designed microbial consortia composed by carefully selected, well characterized beneficial bacteria and fungi displaying diverse biocontrol modes of action. We compared their ability to control shoot and root pathogens when applied separately or in combination as microbial consortia, and across different application strategies that imply direct microbial antagonism or induced systemic plant resistance. We hypothesized that consortia will perform in a more consistent way than single strains inoculants, as they will be able to control a wider range of plant diseases and along more diverse conditions: either one or other strain would do the job in different scenarios. Our results confirmed our hypothesis, revealing that different individual microorganisms were the most effective in controlling the root pathogen Fusarium oxysporum or the foliar pathogen Botrytis cinerea in tomato under different application schemes. Remarkably, the consortia showed consistent control of both, root and shoot pathogens, through both direct and plant mediated mechanisms, always reaching the same protection levels as the best performing single strains. Our findings highlight the potential of microbial consortia for the development of biological control products with enhanced versatility for plant protection against a wider range of diseases.